Effect of melt superheating on solidification microstructure and mechanical properties of K424 superalloy - Jing, Gao-yang; Li, Ao-qi; Sun, Xun; Jin, Lei; Zhou, Cheng; Zhan, Dong-ping; Li, Ji-hang (China foundry, 2025)
The effect of melt superheating treatment on the solidification microstructure and mechanical properties of the γ ’ phase precipitation-strengthened K424 superalloy was investigated. Differential scanning calorimetry (DSC) experiments were conducted to explore the influence of melt treatment temperature on the undercooling of the superalloy. Additionally, pouring experiments were carried out to assess how alterations in both the temperature and duration of melt treatment impacted the grain size, secondary dendrite arm spacing (SDAS), elemental segregation, and mechanical properties of the alloy. Metallographic analysis, scanning electron microscopy, energy dispersive spectroscopy (EDS) and Thermo-Calc software were employed for microstructure characterization. The test specimens were subjected to tensile testing at room temperature and stress rupture testing at 975 °C under 196 MPa. The findings reveal that appropriate melt treatment conditions result in decreased grain size, refined SDAS, minimized elemental segregation, and significant improvements in mechanical properties. Specifically, the study demonstrates that a melt treatment at 1,650 °C for 5 min results in the smallest average grain size of 949 µm and the smallest SDAS of 25.38 µm. Furthermore, the room temperature tensile properties and creep resistance are notably affected by the melt treatment parameters. It is shown that specific melt treatment conditions, such as holding at 1,650 °C for 5 min, result in superior room temperature strength and extended stress rupture life of the K424 superalloy, while a balance between strength and stability is achieved at 1,600 °C with a holding time of 10 min. These findings offer guidance for optimizing the melt treatment parameters for the K424 superalloy, laying a foundation for further investigations.